POOR SLEEP AND REDUCED MOBILITY ARE RISK FACTORS FOR COGNITIVE DECLINE IN METABOLIC SYNDROME. (11th November 2018) - Leritz, E; Bean, J; Ferland, T; McGlinchey, R; Milberg, W
Abstract: Metabolic syndrome (MetS) is associated with cognitive impairment and dementia. Less is known about specific mechanisms that lead to these disease states. We examined whether health-related factors (sleep and mobility) are related to cognition in MetS. 130 older adults (55 MetS) completed a battery of neuropsychological tests as well as measures of sleep quality and mobility (Short Physical Performance Battery; SPBB). When compared to non-MetS, the MetS group reported worse sleep quality (p<.01), and within the MetS group, sleep was associated with poorer performance on tasks of executive function (r=-.47; p<.05). MetS also demonstrated worse SPBB score (p<.05). In a subset of participants, SPBB score was predictive of executive function performance (R2=.536; p <.01). These results suggest that co-occurring vascular risk may negatively impact aspects of sleep and mobility, which may in turn affect aspects of cognition, all of which increase risk for the development of cognitive decline and dementia.